A quantitative classification of OTC medicines regulations in 30 European countries: dispensing restrictions, distribution, pharmacy ownership, and pricing systems - Eduardo Daniel López Vila; Caroline Buts; Marc Jegers (Taylor & Francis Group, 2023)
Abstract Background This paper reviews the regulations of over-the-counter (OTC) medicines in 30 European countries with the goal of identifying the regulatory trends and clusters as of May 2022. Methods To that end, we reviewed the regulation that directly or indirectly might have an impact on OTC medicines. The data were gathered from the national legislation, reports from international organizations, and the existent literature. The 12 regulatory items obtained were classified into four categories: price, pharmacy ownership, distribution modes, and dispensing restrictions. In addition, these items were also employed in the cluster analysis. Results Pharmacy ownership is mainly private, and in the majority of countries, OTC medicines are not subject to any pricing system. Almost every country studied allows online selling of OTC medicines, and 16 countries allow non-pharmacy retail to sell OTC medicines as well. The dispensing restrictions applicable in pharmacy retail are similar in the countries studied: they rely on the staff, OTC medicines are placed behind the counter and the doses dispensed tend to be restricted. Concerning non-pharmacy retail, additional dispensing restrictions might be imposed, such as the establishment of buyers' minimum age, the requirement of a pharmacist to supervise the operations, a regulation on the location in the store, and further restrictions on the package sizes, strength, or pharmaceutical form. The cluster analysis resulted in an initial division between countries that widely allow the sale of OTC medicines in non-pharmacy retail and countries, where pharmacy retail has an OTC monopoly. Based on the regulations, 7 subsequent groups were identified evidencing wide regulatory heterogeneity within the countries studied. Conclusions Our findings point out that OTC medicines are in general not subject to pricing systems, selling is allowed online, and ownership of pharmacies is mostly private. However, regarding dispensing restrictions, pharmacy chains, and establishment restrictions of pharmacies, we found heterogeneity that is also visible in our cluster analysis, since we identified 7 clusters.